The angry, abusive and controlling men in K.S. Maniam’s short story ‘Mala’ / Nurhafizah Ali, Mazni Muslim and Aida Mustapha - Ali, Nurhafizah; Muslim, Mazni; Mustapha, Aida (Universiti Teknologi MARA, 2021)
The fight against sexism has been going on for decades. However, women in the present society still experience gender and social injustice, domestic violence, and sexual harassment on a daily basis. In many cases, conservative families with patriarchal values become a breeding ground for sexism and gender discrimination against women. The bitter reality of sexism and foul treatment experienced by women are exposed through Maniam’s short story ‘Mala’. This study seeks to examine the male characters’ behaviour, attitude, and treatment towards Malati, the main protagonist of the story – and how she deals with the treatment she receives from them. The analysis reveals that the female protagonist is suppressed by her father during childhood, emotionally abused and exploited for free labour by her husband after marriage and oftentimes harassed by her male clients at her workplace. The ill treatment, exploitation, and harassment she receives from men around her from a young age impact her mental health, thus in turn leave her with the feelings of numbness and unworthiness for the rest of her life.